2015
DOI: 10.1016/j.soilbio.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Differential acquisition of amino acid and peptide enantiomers within the soil microbial community and its implications for carbon and nitrogen cycling in soil

Abstract: a b s t r a c t L-isomeric amino acids and oligopeptides are thought to represent a key nitrogen (N) source for plants and soil microorganisms, bypassing the need to take up inorganic N, whilst self-cycling of D-enantiomers within peptidoglycan-containing bacteria may provide a further short circuit within the N cycle. Here we use stable isotope profiling (SIP) to identify the fate of organic N within soil microbial communities. We followed the incorporation of 13 C-labelled D-or L-labelled amino acids/peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…In this study, amino acid contents revealed treatments response similar to that for total microbial PLFAs, bacterial PLFAs and G+ve bacterial PLFAs, as found earlier by Broughton et al (2015). Some other studies also revealed a positive correlation between soil amino acids and microbial N (Geisseler & Horwath, 2008;Hofmockel et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…In this study, amino acid contents revealed treatments response similar to that for total microbial PLFAs, bacterial PLFAs and G+ve bacterial PLFAs, as found earlier by Broughton et al (2015). Some other studies also revealed a positive correlation between soil amino acids and microbial N (Geisseler & Horwath, 2008;Hofmockel et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The microbial utilization of D -amino acids has been studied mainly in soils and is regarded as common in soil microorganisms (e.g., Hill et al, 2011 ; Broughton et al, 2015 ; Radkov et al, 2016 ). D -amino acid utilization by marine microbiota has also been studied (e.g., Perez et al, 2003 ; AzĂșa et al, 2014 ; Shelford et al, 2014 ); however, only a few D -amino acid utilizers have been isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids in both and L-and D-forms can be considered as organic nitrogen and carbon sources for soil microbes [38,39] that can lead to an increase in respiration in soil [40]. However, studies reveal that L-amino acids are more readily taken up by gram-positive bacteria in soil than their D form [38].…”
Section: Discussionmentioning
confidence: 99%